Colloid Deposition Kinetics with Surface-Active Agents: Evidence for Discrete Surface Charge Effects - Litton, Gary M.; Olson, Terese M. (Journal of colloid and interface science, 1994)
Latex particle deposition kinetics in granular quartz beds were compared with and without surface-active agents to evaluate the effects of surface heterogeneities. Hydrophobic regions or metal oxide impurities were masked with sodium dodecyl sulfate (SDS) or phosphate, respectively. Deposition rates exhibited a remarkable ionic strength sensitivity in the presence of 10 -3 M SDS that was similar to unfavorable filtration predictions using DI,VO theory. The strong influence of SDS on particle deposition rates indirectly suggests that particle attachment is enhanced by uncharged, hydrophobic regions of the latex or quartz. Phosphate had little effect on either electrophoretic mobilities or particle deposition rates.